INDIGENOUS WATER MANAGEMENT:WATER CONSERVATION STRATEGIES IN ROTE ISLAND, NUSA TENGGARA TIMUR (NTT) (Manajemen Air Pola Mamar: Strategi Konservasi Air di Pulau Rote, Propinsi Nusa Tenggara Timur (NTT)) - Dua K.S.Y. Klaas (Jurnal Manusia dan Lingkungan, 2009)
ABSTRACTIndigenous knowledge described as part of social and cultural structure of a community is one of tangibel conservation components of water resources. Water management called Mamar System in Rote Island – NTT is a water conservation effort in an island characterized by karst landscape. Hydrogeologically and socially, this system is threatedned by several factors such as population growth, land use modification and global climate change. The objective of this article is tom present recommendation which are conservation strategies based on sustainable water management principles. This paper evaluates potential factors that reduce Mamar System’s capacity in supplying water to the whole communities in Rote Island. As a conclusion several conservation measures are recommended based on sustainable water management principles.ABSTRAKKearifan lokal yang adalah bagian dari struktur sosial dan budaya sebuah masyarakat merupakan salah satu komponen konservasi yang ampuh untuk perlindungan sumber daya air. Manajemen air dengan nama Sistem Mamar di Pulau Rote, NTT adalah bentuk usaha konservasi mata air di pulau yang didominasi oleh geologi karst. Sistem ini secara hidrogeologi dan sosial terancam keberadaannya oleh karena beberapa faktor seperti laju pertambahan penduduk, perubahan tata guna lahan dan perubahan iklim global. Tulisan ini memaparkan faktor-faktor yang berpotensi mengurangi kapasitas Sistem Mamar di Pulau Rote. Di akhir tulisan ini didesain rekomendasi berupa strategi konservasi bertolak dari prinsip manajemen air berkelanjutan.